2002
DOI: 10.1002/dmrr.240
|View full text |Cite
|
Sign up to set email alerts
|

Islet autoantibodies in cord blood: maternal, fetal, or neither?

Abstract: In high-risk type 1 diabetes populations, up to 3% of the general population newborns may express islet autoantibodies in cord blood and the vast majority of those appear to be maternal autoantibodies that disappear usually before the age of 9 months. Despite recent progress in standardization of autoantibody assays, some of the findings appear to be artifacts or non-IgG-mediated binding phenomena. It remains unclear whether transplacentally transmitted maternal autoantibodies play any role in protecting the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Other studies have reported frequencies of around 3%. 44 There was a lower number of high binders in 2001 (0.3%) as compared to the other years (0.6%) due to a downward drift in the GAD65Ab assay during the middle of 2001. However, this underestimation in 2001 likely reduced the significance of our results as a repeat of the analysis with the 2001 newborns omitted showed a stronger consistent seasonal quarterly trend in newborns with high GAD65Ab binding.…”
Section: Discussionmentioning
confidence: 90%
“…Other studies have reported frequencies of around 3%. 44 There was a lower number of high binders in 2001 (0.3%) as compared to the other years (0.6%) due to a downward drift in the GAD65Ab assay during the middle of 2001. However, this underestimation in 2001 likely reduced the significance of our results as a repeat of the analysis with the 2001 newborns omitted showed a stronger consistent seasonal quarterly trend in newborns with high GAD65Ab binding.…”
Section: Discussionmentioning
confidence: 90%
“…TEDDY was designed to obtain blood samples from 3–4 months of age and onwards every three months to detect a first appearing β-cell autoantibody. Since mothers may be β-cell autoantibody positive, whether with T1D (36, 37), or not (25, 3739), we excluded FDR mothers and adjusted for maternal β-cell autoantibody exposure that was determined by analysing IAA, GADA and IA-2A in a blood sample from the mothers when the child was 6–9 months old (1). In our analysis, 51 children were found to be exposed to maternal autoantibodies but there was no association with risk of IAA or GADA in the child.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that transplacental transfer of maternal islet autoantibodies confers an increased risk for type 1 diabetes has been suggested [164] questioned [145,[165][166][167] and discussed in recent reviews [168][169][170]. Even in infants whose mother has diabetes-related autoantibodies, these placentally-transferred autoantibodies almost always fade in infancy, followed by an autoantibody negative period prior to development of autoantibodies usually after age 15 months in young children who subsequently develop T1D [171].…”
Section: Perinatal Factors and Postnatal Growthmentioning
confidence: 98%